Women serving women: Ghana's female livestock keepers - International Livestock Research Institute (International Livestock Research Institute, 2020)
Women in Ghana who keep livestock can improve their economic status and feed their families better. But traditional gender dynamics can make it hard for them to access vaccines for livestock. CARE International, ILRI and a social enterprise called Cowtribe are challenging ingrained gender beliefs about who can own livestock, who can be a vet, and who can have knowledge about livestock. Part of the solution involves actively recruiting women as vets. ‘Men will talk to men’, says Peter Awin, cofounder of Cowtribe. ‘Women can walk into a customer’s kitchen, talk to the woman and ask: ‘Do you have chickens for me to vaccinate?’ Men will not walk into the kitchen and have that conversation.’